ST-depression in right precordial leads with inferior STEMI and occluded right coronary artery: intertwined anatomy and ischemic areas. Issue 5 (3rd September 2017) - De Gennaro, Luisa; Brunetti, Natale Daniele; Ruggiero, Massimo; Rutigliano, David; Locuratolo, Nicola; Di Biase, Matteo; Caldarola, Pasquale
Abstract : Right coronary artery (RCA) occlusion in inferior acute myocardial infarction is usually heralded by ST-elevation both in inferior and in right precordial leads. We report the case of a 68-year-old male, who presented marked ST-elevation in inferior leads, mirrored by ST-depression in anterior-septal and lateral leads. Right precordial lead electrocardiogram unexpectedly showed ST-depression V1R–V5R leads. Coronary angiography showed mid-left anterior descending (LAD) coronary near-complete occlusion with distal wrapping LAD. Left circumflex artery was not occluded, while RCA was occluded mid tract. The patient was treated with coronary angioplasty on RCA and LAD. Absence of ST-elevation in right precordial leads may be presumably explained by the presence of a large ischemic area distal to mid-LAD near-occlusive stenosis and of a long-wrapping LAD. Complex coronary anatomy and intertwined ischemic areas may underlie apparently discording electrocardiograms.